The impact of trade policy on the export of agricultural products of Azerbaijan - Nazakat Musayeva; Nigar Atakishiyeva; Ulkar Mammadova; Gulnara Tanriverdiyeva; Оlena Lemishko (Наукові горизонти)
The study presented a comprehensive analysis of the factors affecting the competitiveness of agricultural products in Azerbaijan, with an emphasis on assessing the role of trade policy and government support. The main focus was on the impact of trade agreements, tariff and non-tariff barriers, and subsidy programmes on export volumes. Using the methods of statistical and comparative analysis, the main determinants affecting the export of agricultural products were identified and their importance is assessed. The purpose of the study was to develop effective measures and strategies to improve the export potential and increase the competitiveness of Azerbaijan’s agricultural sector in international markets through the analysis of key factors and the impact of trade policy. The results of the study showed that Azerbaijan’s participation in international trade agreements has a positive impact on export performance. The conclusion of bilateral agreements with key trading partners such as the EU, Turkey, and Iran contributed to the reduction of trade barriers and the opening of new markets. This highlighted the importance of the country's continued active participation in global trade initiatives. The analysis also confirmed the substantial impact of government subsidies on the competitiveness of products. Targeted subsidies helped to reduce the cost of production and improve quality, which is especially important in the context of international competition. Measures were proposed to optimise subsidy programmes and improve efficiency. Special attention is paid to the role of tariff and non-tariff barriers, which remain a considerable obstacle to exports. The study showed that high tariffs and strict non-tariff requirements substantially limit export potential. In this regard, it is recommended to continue the unification of standards with international requirements and simplify certification procedures. The results of the study emphasised the need to modernise the agricultural sector and introduce innovations. The introduction of modern technologies and the improvement of logistics infrastructure contributed to an increase in export volumes and strengthen positions in international markets. Thus, the study identified the main factors affecting the export of agricultural products of Azerbaijan and proposes specific measures to improve trade policy and increase the competitiveness of products in international markets